Direct and indirect effects of self-directed learning on creativity in healthcare undergraduates: a chain mediation model of openness to challenge and diversity and creative self-efficacy - Jiazhen Qian; Xiang Li; Ting Liu; Mengfan Zhang; Kaiyan Li (Frontiers in Psychology, 2023)
BackgroundCreativity and self-directed learning (SDL) are prominent for undergraduate healthcare students to provide quality patient care in an increasingly complex healthcare environment. Research suggested that SDL is linked with creativity, yet the mechanism underlying the relationship between SDL and creativity has not been fully understood.ObjectiveThis study examined the relationship between SDL and creativity and constructed a chain mediation model to identify the mediating effect of openness to diversity and challenge (ODC) and creative self-efficacy (CSE).MethodsThrough convenience sampling, 575 healthcare undergraduates (average age = 19.28 years, SD = 1.124 years) were surveyed from Shandong Province in China. Creativity, SDL, ODC, and CSE were assessed using corresponding scales. Pearson’s correlation analysis, hierarchical multiple linear regression analysis, a serial multiple mediation analysis, and bias-corrected percentile Bootstrap method were conducted by using structural equation modeling by AMOS 26.0.ResultsThe direct path between SDL and creativity was significant. SDL can positively predict both ODC and CSE, and the latter two variables can significantly and positively predict creativity. ODC and CSE played a significant partial mediating role in the relationship between SDL and creativity. The mediating effect consists of three indirect effects: SDL → ODC → creativity (the mediating effect value is 0.193, p = 0.012), SDL → CSE → creativity (the mediating effect value is 0.096，p = 0.001), and SDL → ODC → CSE → creativity (the mediating effect value is 0.035, p = 0.031).ConclusionSDL can positively predict creativity. ODC and CSE had significant mediating effects between SDL and creativity, including single partial mediating effects of ODC and CSE and chain mediating effects of ODC-CSE.